Neutralization of Galena Acid Mine Water Using CaO and CaCO₃ at PT Berkat Bhinneka Perkasa - Zulhaji Sam, Taufik; Mukhlis, Mukhlis; Aththorick, T Alief; Harahap, Hamidah; Muzambiq, Said (Tunas Geografi, 2024)
The mining system implemented at PT. Berkat Bhinneka Perkasa is an underground mining system. The results from mining the metal mineral commodity black lead ore (PbS/Galena) are helpful in the battery industry, color pigments, ammunition, cable coatings, radiation protection, solder, and other materials that use Pb and Zn as basic ingredients. This research examines the neutralization of acid mine drainage using Tohor Lime (CaO) and Calcium Carbonate Lime (CaCO3). The methods used are survey and experimental techniques, where the survey involves field observations to determine observation points and collect data. In contrast, the experimental method includes laboratory analysis followed by data analysis. This research shows that acid mine wastewater with pH 4.74 and 240.20 ppm Fe²⁺ was effectively treated using quicklime, calcium carbonate, TKKS, and rice husk biochar. These ameliorants significantly increased pH and met the river water quality standards per Government Regulation 22 of 2021. Although active ferrous levels also increased, the effect was not statistically significant. However, excessive ferrous content can harm agricultural soils and plants, potentially causing iron toxicity.